Cultural and digital literacy in rural indonesian elementary schools: a case study from Melawi - Mastiah; Mardiana; Rokiah Paee; Tri Marhaeni Pudji Astuti; Muhammad Akip (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
The present study examines the implementation of cultural and digital literacy in elementary schools in Melawi Regency, Indonesia, a rural area rich in cultural traditions, yet constrained by limited digital infrastructure. This study addresses a gap in previous research, which has not explored the relationship between these two forms of literacy within rural school contexts. This research aims to analyze the implementation of cultural and digital literacy by examining teacher training, classroom practices, the availability of learning resources, and the integration of folklore into instruction. Using a qualitative case study design, data were collected from 22 schools through classroom observations and semi-structured interviews with 22 principals and 22 teachers. The data were analyzed using descriptive qualitative analysis supported by a coding process applied to interview transcripts and observation notes. The findings indicate that: (1) teacher training remains limited, with only 15 schools participating in short district-level workshops; (2) cultural literacy was present in a majority of schools, with folklore integrated into learning activities in 13 out of 22 schools, although the frequency of use varied; and (3) digital literacy has not yet developed due to unstable electricity, weak internet connectivity, and limited opportunities for student engagement. This study contributes to the literature by demonstrating how cultural literacy continues to develop despite digital constraints and filling a research gap concerning the integration of cultural and digital literacy in rural elementary schools.